2009
DOI: 10.1097/sle.0b013e3181a822f8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Xanthogranulomatous Cholecystitis

Abstract: Surgical treatment remains the most effective and feasible option for XGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
3
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 11 publications
6
73
3
3
Order By: Relevance
“…Analysis of data from outside of China has shown that, in 65% of XGC cases, complete cholecystectomy was difficult, and 35% of cases underwent partial cholecystectomy. 1 In the present study, the mean duration of surgery was 114.6 minutes, which is longer than that for common open cholecystectomy, illustrating the difficulty of surgery in XGC patients. Complete cholecystectomy was performed in 9 patients, and partial cholecystectomy was performed in 5 patients with severe adhesions of the gallbladder to neighboring tissue.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Analysis of data from outside of China has shown that, in 65% of XGC cases, complete cholecystectomy was difficult, and 35% of cases underwent partial cholecystectomy. 1 In the present study, the mean duration of surgery was 114.6 minutes, which is longer than that for common open cholecystectomy, illustrating the difficulty of surgery in XGC patients. Complete cholecystectomy was performed in 9 patients, and partial cholecystectomy was performed in 5 patients with severe adhesions of the gallbladder to neighboring tissue.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is largely related to the difficulty of stripping the gallbladder, mode of surgery, and physical condition of the patient. 1,12 Complications occurred in 2 (14.2%) patients in the present study: hematoma (n ¼ 1) and pneumonia (n ¼ 1). None of the patients in the present study died.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Während sich für die Suchbe griffe "xanthogranulomatous sialadenitis" und "xanthogranulomatous + parotid" lediglich 7 Fallberichte in der PubMed Datenbank ergeben [5,6,10,13,18,27,28], trifft man für andere Lokalisationen wie Gallenblase oder Niere auf größere Fall serien von bis zu 74 Fällen pro Studie [16,29]. Dies deutet auf eine große Seltenheit xanthogranulomatöser Veränderungen in den Speicheldrüsen hin.…”
Section: Hintergrundunclassified